STIMULASI KECERDASAN SPIRITUAL PADA ANAK USIA DINI MELALUI KISAH - Sidik Nuryanto (JURNAL INDRIA (Jurnal Ilmiah Pendidikan Prasekolah dan Sekolah Awal), 2017)
Spiritual intelligence is an important part of early childhood development. The story as one of the storytelling method that raised the Islamic story to be a guide for children in stimulating spiritual intelligence. This method is relevant if used for early childhood, because they know the value is still using his imagination. As in the story can raise the story of the life of the Prophets, Rosul, as well as the companions who do have a good track record of morals. Hopefully the lesson or moral message of the story can inspire children to apply in everyday life.